Planejamento da família integrado ao planejamento estratégico pessoal - Fleig, Giovana Bortoluzzi (2013)
Strategic planning is naturally applied to organizations to compete and deal with change. Just as an organization can adopt strategic planning to achieve their goals, an individual can plan your life so anticipate change, seize opportunities and achieve self-actualization. Strategic planning is a method of personal life management that covers several areas (professional, individual, family, personal business and social participation). In the family, it allows the person to make informed decisions and control the consequences of these relationships, preventing conflict. That is especially important in the family business. The objective of this paper is to propose a model of family planning to deal with emotional and legal relationships between spouses, parents, children and grandparents, contributing to the personal strategic planning. This is an bibliographical exploratory qualitative research. The literature review allowed to identify the variables to the model. At the end, it was presented a model to guide the affective and legal relationships planning. This allows the individual to make informed decisions and control the consequences of these relationships. The proposed model does not replace the personal strategic planning models consolidated, but can be used in a complementary way.